Producing a recombinant vector that carries the vascular class III peroxidase (\(PRX1\)) gene from \(Catharanthus roseus\) - Cao, Thi Thu Thuy; Nguyen , Thi Bich Ngoc; Nguyen, Duc Quan; Le, Tat Thanh; Nguyen, Huy Hoang; Huynh, Thi Thu Hue (Academia Journal of Biology, 2023)
Terpenoid indole alkaloids (TIAs) vincristine and vinblastine are two essential anticancer drugs used in cancer treatments. These compounds are naturally available only in Catharanthus roseus in low accumulation, leading to efforts to upregulate TIAs substances through other expression organisms. The combination of vindoline and catharanthine into α-3∼,4∼-anhydrovinblastine (AVLB) is an important step for the biosynthesis of vinca alkaloids, which serves as a precursor to vinblastine and vincristine. Vascular class III peroxidase (PRX1) plays a crucial role in catalyzing the dimerization reaction. In this study, we created a recombinant plasmid consisting of the PRX1 gene with the aim to transform and express it stably in fungi. The full-length 1092 bp C. roseus PRX1 coding sequence was optimized to be suitable for a fungal translation system while keeping its amino acid sequence unchanged. The pGreen3 vector was used as the backbone to harbor the PRX1 and hygromycin-resistant gene (HYG)- which enabled fungi cells to survive in the HYG selection medium. This HYG gene was cut from the pGreen2 vector and inserted into the pGreen3 vector. Both PRX1 and HYG genes are located between the gpdA promoter and TrpC terminator structure. The recombinant plasmids were screened and amplified by transformation into Escherichia coli DH10B, and cultured in the LB medium containing kanamycin antibiotic. Our recombinant vector is suitable for further expression into endophytic fungi.